Adolescent volunteerism and its contributions to social and moral development as perceived by the UPLB Ugandan ng Pahinungod student volunteers - Lalap, Belinda A.; Dy, Marison R.; Saguiguit, Sue Liza C.; Dizon, Josefina T. (2012)
This study was conducted to determine the relationship between the adolescents' demographic and personal attributes, namely: age, student classification, religious involvement, birth order, sex empathy, and personal distress with their motivations for volunteerism, specifically: self-esteem, social relationship, reciprocity, recognition, and career development. The respondents' perceived contributions of volunteering to their social and moral developmental domains were also determined.

Fifty Ugnayan ng Pahinungod student volunteers from the University of the Philippines Los Banos, aged 16 to 21 years old, were asked to accomplish self-administered questionnaires. Descriptive analysis was used to determine the respondents' demographic and personal attributes and their perceived contributions of volunteerism to social and moral development while Spearman correlation test and cross-tabulations were used to determine the relationship between adolescents' demographic and personal attributes and motivations.